Climate Change and Indigenous Peoples in the United States Impacts, Experiences and Actions - Maldonado, Julie Koppel; Colombi, Benedict; Pandya, Rajul (Springer International Publishing : Imprint: Springer, 2014)
With a long history and deep connection to the Earth's resources, indigenous peoples have an intimate understanding and ability to observe the impacts linked to climate change. Traditional ecological knowledge and tribal experience play a key role in developing future scientific solutions for adaptation to the impacts. The book explores climate-related issues for indigenous communities in the United States, including loss of traditional knowledge, forests and ecosystems, food security and traditional foods, as well as water, Arctic sea ice loss, permafrost thaw, and relocation. The book also highlights how tribal communities and programs are responding to the changing environments. Fifty authors from tribal communities, academia, government agencies, and NGOs contributed to the book. Previously published in Climatic Change, Volume 120, Issue 3, 2013.